The cortico-basal ganglia integrative network: the role of the thalamus - Haber, Suzanne N. (Brain Res Bull, 2008)
The thalamus is a critical component of the frontal cortical-basal ganglia-thalamic circuits that mediate motivation and emotional drive, planning and cognition for the development and expression of goal-directed behaviors. Each functional region of the frontal cortex is connected with specific areas of each basal ganglia (BG) structure and of the thalamus. In addition, the thalamus sends a massive, topographically organized projection directly to the striatum. Tract-tracing and physiological experiments have indicated a general topographic organization of the cortical-BG-thalamic loops and supported a model of BG function based on parallel and segregated pathways. However, the learning and execution of appropriate behavioral responses require integration of inputs related to emotional, cognitive, and motor cortical functions. Our recent data indicate that integration may occur via non-reciprocal connections between the striatum and substantia nigra and within “hot spots” of convergence between cortico-striatal projections from different functional regions. Similarly, integration may exist in the thalamus. There are non-reciprocal connections between the thalamus and cortex via thalamocortical projections that terminate in the superficial and deep cortical layers. These terminals can influence different functional cortical areas that, in turn, project to the striatum and back to the thalamus. In addition, a non-reciprocal corticothalamic projection terminates in thalamic regions that are parts of other circuits. Finally, ‘hot spots’ of convergence between terminals from different cortical regions may also occur in the thalamus as is seen in the striatum. Thus, via several different pathways, the thalamus may serve as an important center of integration of networks that underlie the ability to modulate behaviors.